Poor sensitivity of multiple-gated blood-pool imaging in diagnosing left ventricular aneurysms. Issue 6284 (11th July 1981) - Allen, A P; Peart, I; Taylor, D N; Condon, B R; Ogilvie, B C; Frank, J W; Sutton, H; Ackery, D M
Abstract : A study was carried out to determine the accuracy of multiple-gated blood-pool imaging in diagnosing left ventricular aneurysm. Fifteen patients with an aneurysm and 17 with left ventricular hypokinesia were studied by contrast ventriculography and multiple-gated blood-pool imaging. The results of blood-pool imaging were examined blind by five independent observers, the results of contrast ventriculography being used as the standard. The mean sensitivity of the procedure was 56%, the specificity 61%, and diagnostic accuracy 59%. These results indicate that contrast ventriculography remains the best method for diagnosing left ventricular aneurysms. Moreover, ventriculography provides additional information-for example, on wall thickness-not provided by multiple-gated blood-pool imaging.